Genetika in farmakogenetika Gilbertovega sindroma - Ostanek, Barbara (Farmacevtski vestnik, 2009)
Gilbert's syndrome is the most common hereditary disorder of bilirubin metabolism. Mild unconjugated hyperbilirubinemia results from decreased activity of UDP-glucuronosyltransferase 1A1 due to polymorphisms in the UGT1A1encoding gene. Polymorphisms in the gene encoding organic anion transporter SLCO1B1 can reduce the hepatic uptake of unconjugated bilirubin and also contribute to hyperbilirubinemia. Besides bilirubin, several drugs are also substrates for glucuronidation with UGT1A1 or hepatic uptake by SLCO1B1. Polymorphisms in both genes associated with Gilbert's syndrome have therefore important implications for individualised therapy. Their impact on pharmacokinetic profile and therapeutic or side effects has been best described for irinotecan and pravastatin.
Keywords: drug; Gilbertov sindrom; hiperbilirubinemija; polimorfizem; toksičnost; zdravila